2016
DOI: 10.3329/medtoday.v27i2.30038
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profile of NSTEMI (Non ST Elevation Myocardial Infarction) Patients & Association of ST-Segment Depression and Level of Troponin I with NSTEMI Patient's In-Hospital Outcome

Abstract: Acute coronary syndrome (ACS) remains the leading cause of death in the developed world and second leading cause of death in developing countries. Elevated troponin levels and extent of ST-segment depressions are clinically important because they may act as an effective prognostic marker .This cross-sectional study has been designed to see the correlation of ST-segment depression and level of troponin I with in-hospital outcome of NSTEMI patients. The study was conducted in the Department of Cardiology, Dhaka … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
(21 reference statements)
5
7
0
Order By: Relevance
“…Also, Killip classification was a powerful independent predictor of NSTE-ACS [16][17][18]. Additionally, some other studies have suggested that factors such as age, heart rate, systolic BP, ST-segment depression and cardiac enzymes as the strongest predictor of mortality and MI [19,20]. Results of these studies are in line with the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Also, Killip classification was a powerful independent predictor of NSTE-ACS [16][17][18]. Additionally, some other studies have suggested that factors such as age, heart rate, systolic BP, ST-segment depression and cardiac enzymes as the strongest predictor of mortality and MI [19,20]. Results of these studies are in line with the current study.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that 35 (70.0%) patients of group A were smoker and 33 (66.0%) patients of group B were smoker; difference was not statistically significant (p=0.668). Zahid et al, (2015) in their study reported similar findings [21].…”
Section: Discussionsupporting
confidence: 70%
“…The majority of the patients of the present study were male (84.8% and 88.2% in group I and group II respectively), such male predominance was also reported by other researchers. 13 The gender disparity in the present study may be multifactorial e.g., lower prevalence of CAD in women, less health-care seeking attitude of females and relative unwillingness for invasive procedures. Regarding CAD risk factors, smoking, hypertension and family history of CAD did not differ significantly between the groups.…”
Section: Discussionmentioning
confidence: 71%
“…The mean age of patients in group I and II was 52.7±8.9 and 50.9±9.7 years respectively. In a study conducted at Dhaka Medical College by Zahid et al 13 the mean age of NSTEMI patients was 55.9±9.1 years. The majority of the patients of the present study were male (84.8% and 88.2% in group I and group II respectively), such male predominance was also reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%